Information Literacy: Information Sharing, Democracy and Life-long learning - Maguire, Betty (Qualitative and Quantitative Methods in Libraries, 2017)
Information Literacy (IL) is becoming an increasingly important skill in today’s technology driven world. This paper examines some typical definitions of IL . Three specific models of IL, the Inquiry Learning Model, The Sconul Seven Pillars of IL Model, and the Digital Information Fluency Model, are then explored. The Junior Cert School Programme (JCSP) , a functional and  information literacy programme  directed at young people deemed at risk of  leaving school early, is discussed using details of correspondence between the author and Kathleen Moran, Senior JCSP Project Librarian. Finally, Information Literacy in relation to copyright, with emphasis on the recently published consultation paper of the review committee of the Copyright and Related Acts 2000 (CRRA) is discussed.